2019
DOI: 10.1089/cbr.2019.2829
|View full text |Cite
|
Sign up to set email alerts
|

Nucleobindin-2 Promotes the Growth and Invasion of Glioblastoma

Abstract: Background: Glioblastoma is one of the most malignant tumors in the brain with high mortality. In recent years, immunotherapy and targeted therapy show great prospects in the treatments for glioblastoma, whereas more effective therapeutic targets are still urgently needed to be developed. Nucleobindin-2 (NUCB2) is the precursor protein of nesfatin-1, which have a variety of metabolic functions, such as food intake and temperature regulation. In recent years, the potential link between NUCB2 and the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…Liu et al found that the mRNA expression level of NUCB2/NESF-1 in glioblastoma was significantly higher than in normal tissues ( p < 0.05, n = 163) [ 58 ]. The IHC staining showed that NUCB2/NESF-1 was predominantly expressed in the nucleus and was highly overexpressed in glioblastoma compared to the adjacent tissue [ 58 ]. Moreover, it was noticed that the high expression of NUCB2/NESF-1 was related to the recurrence.…”
Section: Nucb2—a Predictive/prognostic Biomarker In Cancers?mentioning
confidence: 99%
See 2 more Smart Citations
“…Liu et al found that the mRNA expression level of NUCB2/NESF-1 in glioblastoma was significantly higher than in normal tissues ( p < 0.05, n = 163) [ 58 ]. The IHC staining showed that NUCB2/NESF-1 was predominantly expressed in the nucleus and was highly overexpressed in glioblastoma compared to the adjacent tissue [ 58 ]. Moreover, it was noticed that the high expression of NUCB2/NESF-1 was related to the recurrence.…”
Section: Nucb2—a Predictive/prognostic Biomarker In Cancers?mentioning
confidence: 99%
“…As a result, there is a need to identify new proliferation-related molecules in cancers. In vitro studies showed that NUCB2/NESF-1 knockdown with siRNA or shRNA in breast cancer (MCF-7, SKBR-3), bladder cancer (T24, 5637), glioblastoma (U251, U87), endometrial cancer (Ishikawa and Sawano), and thyroid cancer (TPC-I, KI) cell lines resulted in the inhibition of cell proliferation [ 41 , 47 , 50 , 53 , 58 ]. Moreover, proliferation-related proteins (Ki-67 and PCNA) were decreased in NUCB2/NESF-1 shRNA-transfected thyroid cancer cells compared to the control.…”
Section: Nucb2 In Cancer Proliferation Apoptosis Migration and Invasionmentioning
confidence: 99%
See 1 more Smart Citation
“…The immunoreactivity of Nucb2 was mainly detected in the cytoplasm of cancer cells [ 13 , 22 , 23 ]. However, in glioblastoma cancer cells [ 24 ], the localization of Nucb2 was nuclear. In most cases, Nucb2 expression was correlated with the key clinicopathological characteristics of cancer.…”
Section: Nucb2 Involvement In Cancer Progressionmentioning
confidence: 99%
“…Moreover, in vivo studies also showed that the knockdown of Nucb2 might decrease tumor growth, at least in the case of thyroid and bladder cancer cells [ 20 , 26 ]. In addition, lung metastases were not observed in cells with Nucb2 suppression [ 24 , 26 ]. All of the above-mentioned analyses indicate that Nucb2 is linked in a tissue-specific manner to tumor development and metastasis, both in vitro and in vivo.…”
Section: Nucb2 Involvement In Cancer Progressionmentioning
confidence: 99%